2022
DOI: 10.1155/2022/9015778
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based Brain Tumor Detection Model Using Local Binary Pattern and Multilayered SVM Classifier

Abstract: In this paper, an autonomous brain tumor segmentation and detection model is developed utilizing a convolutional neural network technique that included a local binary pattern and a multilayered support vector machine. The detection and classification of brain tumors are a key feature in order to aid physicians; an intelligent system must be designed with less manual work and more automated operations in mind. The collected images are then processed using image filtering techniques, followed by image intensity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The LBP method was used after improving brain tumor images with CNN and was reported to have obtained excellent results. The success rate achieved within the scope of that study was reported as 99.23% [15]. Pattanaik et al used KNN to improve brain tumor MRI images by combining the properties of GLCM, HOG, and LBP in the 2022 study.…”
Section: Related Studiesmentioning
confidence: 95%
“…The LBP method was used after improving brain tumor images with CNN and was reported to have obtained excellent results. The success rate achieved within the scope of that study was reported as 99.23% [15]. Pattanaik et al used KNN to improve brain tumor MRI images by combining the properties of GLCM, HOG, and LBP in the 2022 study.…”
Section: Related Studiesmentioning
confidence: 95%
“…Based on this technique, the authors obtained 98% accuracy. Work in [30] suggested an intelligent design for identifying and classifying MR images using CNN, local binary patterns (LBP), and a multilayered SVM. Through these operations, they attained 99.3% accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, you can have information in which its classification is given by multiple categories. This is very useful in different fields, for example for the detection of cervical cancer [3], other applications can be seen in the detection of brain tumors [4], to segment the client [5], [6], categorize images [7], classify to categorize audios [8] and analyze text to optimize customer sentiment [9]. Data classification techniques have great relevance in different areas, in particular there are abundant information on the technique of support vector machines related to classification [10], because there are not many software related to data classification that use the technique.…”
Section: Introductionmentioning
confidence: 99%